Conjugated fatty acids drive ferroptosis through chaperone-mediated autophagic degradation of GPX4 by targeting mitochondria - Yusuke Hirata; Yuto Yamada; Soma Taguchi; Ryota Kojima; Haruka Masumoto; Shinnosuke Kimura; Takuya Niijima; Takashi Toyama; Ryoji Kise; Emiko Sato; Yasunori Uchida; Junya Ito; et al. (Cell Death and Disease)
Abstract Conjugated fatty acids (CFAs) have been known for their anti-tumor activity. However, the mechanism of action remains unclear. Here, we identify CFAs as inducers of glutathione peroxidase 4 (GPX4) degradation through chaperone-mediated autophagy (CMA). CFAs, such as (10E,12Z)-octadecadienoic acid and α-eleostearic acid (ESA), induced GPX4 degradation, generation of mitochondrial reactive oxygen species (ROS) and lipid peroxides, and ultimately ferroptosis in cancer cell lines, including HT1080 and A549 cells, which were suppressed by either pharmacological blockade of CMA or genetic deletion of LAMP2A, a crucial molecule for CMA. Mitochondrial ROS were sufficient and necessary for CMA-dependent GPX4 degradation. Oral administration of an ESA-rich oil attenuated xenograft tumor growth of wild-type, but not that of LAMP2A-deficient HT1080 cells, accompanied by increased lipid peroxidation, GPX4 degradation and cell death. Our study establishes mitochondria as the key target of CFAs to trigger lipid peroxidation and GPX4 degradation, providing insight into ferroptosis-based cancer therapy.